Dilema Hukuman Mati: Komparasi Antara Konvenan International Terkait Hak Asasi Manusia dan Pandangan Nahdlatul Ulama - Kiagus Zaenal Mubarok; Dina Yulianti; Otong Sulaeman (Jurnal Keislaman, 2023)
The United Nations, through Resolution 77/2022 of the Global Moratorium on the Death Penalty, has encouraged world countries to postpone the death penalty because it is seen as a violation of Human Rights. In this article, the authors compare the arguments by the United Nations and human rights organizations in abolishing the death penalty with the religious views of the largest Muslim organization in Indonesia, Nahdlatul Ulama (NU). The research was conducted using qualitative methods, and data collection techniques were conducted through interviews with informants, namely several Nahdlatul Ulama women activists, as well as literature studies. NU generally approves of the death penalty for perpetrators of serious crimes, such as corruption and subversive acts that threaten national security, as long as there are solid and convincing evidences. NU stated that Islam recognizes the principle of human rights, but the death penalty can be applied to severe crimes to protect the security of the state and protect the right to life of more people. In this study, it was also found that Islamic law (in this case, the verses of the Quran) were in line with the Criminal Code and laws in Indonesia regarding the death penalty.